APPLICATION OF THE DCF MODEL IN CONDITIONS OF HIGHLY VOLATILITY OF COMMODITY MARKETS (ON THE EXAMPLE OF OIL AND GAS COMPANIES) (American Journal of Technology and Applied Sciences, 2025)
This article systematizes the practices of adapting DCF to commodity companies: constructing probabilistic scenarios and stochastic price trajectories (including taking into account mean reversion), Monte Carlo DCF, matching the discount rate to risks, specificity of terminal value for depletable assets, and integration of management flexibility through real Options. Using public reporting materials from oil and gas companies, this article demonstrates how scenario-based "price corridors" and stress tests are used in corporate practice.